2001
DOI: 10.1046/j.1365-2141.2001.02668.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of outcome after intensified therapy of childhood lymphoblastic leukaemia: results from Medical Research Council United Kingdom acute lymphoblastic leukaemia XI protocol

Abstract: Summary. The single most important prognostic determinant in childhood acute lymphoblastic leukaemia (ALL) is effective therapy and changes in therapy may influence the significance of other risk factors. The effect of intensified therapy on the importance of currently recognized phenotypic and genotypic determinants of outcome was assessed in 2090 children enrolled on the Medical Research Council United Kingdom acute lymphoblastic leukaemia XI (MRC UKALL XI) protocol. Treatment allocation was not determined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
95
2
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(107 citation statements)
references
References 43 publications
(60 reference statements)
6
95
2
4
Order By: Relevance
“…Cytogenetically visible 9p abnormalities have been reported to confer an adverse clinical outcome (Hann et al, 2001), whereas recent data on specific loss of CDKN2A showed no link with outcome (van Zutven et al, 2005;Mirebeau et al, 2006;). All 9p deletions in our series encompassed the CDKN2A locus.…”
Section: Discussionmentioning
confidence: 99%
“…Cytogenetically visible 9p abnormalities have been reported to confer an adverse clinical outcome (Hann et al, 2001), whereas recent data on specific loss of CDKN2A showed no link with outcome (van Zutven et al, 2005;Mirebeau et al, 2006;). All 9p deletions in our series encompassed the CDKN2A locus.…”
Section: Discussionmentioning
confidence: 99%
“…However, in multivariate models, Hb was not identified as an independent risk factor. 3,4 Despite the fact that Hb is not applicable for risk stratification in clinical trials, the relationship between anemia and prognosis might hold some important biological information that warrants further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated a correlation between degree of anemia and survival. [1][2][3][4] Evidence suggests that patients presenting with higher hemoglobin (Hb) levels at diagnosis have an increased risk of poor outcome compared to patients with lower Hb levels. However, in multivariate models, Hb was not identified as an independent risk factor.…”
Section: Introductionmentioning
confidence: 99%
“…At least 32% of the ALL cases show clonal chromosomal abnormalities (11). The so-called Philadelphia (Ph) chromosome t(9;22) is present in 4% of pediatric ALL patients and confers an unfavorable prognosis, particularly when associated with either a high whole blood cell count (WBC) or slow early response to initial therapy (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%